PENGARUH PEMBERIAN SUSU KEDELAI (GLICINE MAX L. MERR) TERHADAP KADAR HDL DAN LDL PADA WANITA MENOPAUSE (STUDI PADA IBU - IBU PENGAJIAN AISYIYAH RANTING MELATI MEDAN) - MASYITHAH PRATIWI; AMELIA EKA DAMAYANTY (JURNAL ILMIAH KOHESI, 2020)
The estrogen hormone in women has a function to improve blood cholesterol profiles, by increasing levels of High DensityLipoprotein (HDL) and decreasing Low Density Lipoprotein (LDL). But when women experience menopause the productionof the hormone estrogen will decrease, so women are more susceptible to experiencing dyslipidemia. Phytoestrogens insoybeans have activities such as estrogen which are useful for reducing LDL and increasing HDL. To determine the effect ofgiving soybean milk (Glicine Max L. Merr) on HDL and LDL levels in menopausal women (Study on Women Aisyiyah MelatiMelati Medan Study). The study was an experimental study with one group pretest posttest by giving soy milk for 3 months.The mean HDL levels before and after treatment were 56.90 mg / dl and 57.00 mg / dl with a p value 0.326 (p> 0.05). Themean LDL levels before and after treatment were 145.85 mg / dl and 133.47 mg / dl with a p value 0.0001 (p <0.05). Givingsoy milk has an effect on LDL levels and has no effect on HDL levels in menopausal women.